URGENSI PEMBERIAN SANKSI BAGI PEMILIK IZIN TERHADAP PENYALAHGUNAAN IZIN USAHA PENGINAPAN DI KOTA LUBUKLINGGAU - Muthahir, Ardi; Elvionita, Septiara; Azani, Adila (LPPM Universitas Bina Insan, 2025)
The misuse of lodging business permits in Lubuklinggau City has raised legal, administrative, and ethical concerns, highlighting weaknesses in local regulatory enforcement. This study aims to analyze the legal framework and the urgency of imposing administrative sanctions on business owners who violate licensing regulations, as well as to evaluate the effectiveness of these sanctions in supporting law enforcement and public order. The research employs a normative juridical method with a statutory and conceptual approach, relying on primary legal sources such as legislation and secondary materials including scholarly articles, books, and legal documents. The findings reveal that the regulation of sanctions for the misuse of lodging business permits remains fragmented across multiple regional regulations, resulting in legal uncertainty and inconsistent enforcement. The absence of a comprehensive regulatory mechanism weakens administrative control and reduces compliance among lodging business owners. Consequently, the implementation of clear, firm, and proportional sanctions is essential to strengthen administrative law enforcement, ensure legal certainty, promote fair competition, and realize the principles of good governance within the local tourism sector. Keywords: Administrative sanctions, business permit, lodging industry, local regulation